Polyethyleneimine-protein interactions and implications on protein stability - Mazzaferro, Laura (2010)
Protein stability assessment of seven model proteins in the presence of low molecular weight polyethyleneimine (PEI, MW 2000Da) was performed. Thermodynamic stability, monitored by circular dichroism (CD) spectroscopy, showed that the polymer did not have a major effect on the melting temperature (T m ) of the basic proteins - muscle lactate dehydrogenase (LDH), ribonuclease A, lysozyme and cutinase, while for the acidic ones - human growth hormone, human serum albumin and heart lactate dehydrogenase - there was a shift in T m towards lower temperatures. The secondary structures of the basic proteins were essentially the same, with none or a slight increase in the CD spectra, in presence of the polymer. In the case of the acidic proteins, the CD spectra were diminished mostly due to phase separation. Assuming a homogeneous distribution of the net charge on the protein surface a quantitative inverse relationship was established between surface charge density of the acidic proteins and the PEI 2000 concentration required for maximum flocculation. Despite lowering the thermal stability of acidic proteins, PEI 2000 was seen to protect heart LDH at an increasing oxidative stress.